The Euro-Mediterranean Partnership and the Algerian Economy: An Analytical Study of Motivations, Trade, and Industrial Exports - Saadane, Mahfoudh; Elbarouni, Elyas Abobaker (Sharwes Scientific Journal, 2026)
The Euro-Mediterranean Partnership is considered a strategic framework for economic cooperation between the two shores of the Mediterranean. Through it, Algeria seeks to enhance its integration into the regional and international economy by promoting trade exchange and developing its industrial exports. The problem of the study is represented by the main question: to what extent has the Euro-Mediterranean Partnership contributed to supporting the Algerian economy through trade exchanges and industrial exports? The study aims to analyze the motivations and reasons behind the Euro-Mediterranean Partnership, examine the structure, development, and effects of trade exchanges between Algeria and the European Union. The study relied on the descriptive and analytical methods to describe, analyze, and study trade and industrial export data to understand the impact of the partnership on the Algerian economy. The study reached the main findings, which indicate that despite the benefits, The programs faced challenges related to bureaucracy, weak institutional coordination, and sometimes a misalignment of objectives with national priorities. The benefits of the partnership programs varied across different sectors, necessitating a review of policies and the setting of clear priorities. The study recommends working on enhancing coordination between Algerian institutions and European entities to ensure the achievement of common goals and supporting the participation of the Algerian private sector in industrial and commercial projects linked to the Euro-Mediterranean partnership.